2017
DOI: 10.1515/cerce-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Potential, Cultivation and Quality of Some Crambe Sp. in Southern Turkey

Abstract: ABSTRACT. Crambe sp. is an oilseed crop from the Brassicae family and native to the Mediterranean region. It can be converted into a number of industrial and energy uses. Crambe oil is used in introducing in stain, primers, plastic and solid wax, cosmetic and engine portions in the form of nylon-13.13 exclude carburetor as eco-friendly. All these properties make it interesting. This study is the first report on yield, cultivation procedure, and quality characteristics of Crambe sp. cultivated in Turkey. Native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In other studies, the diameter of crambe (Crambe abyssinica) seeds was 2.7 mm (Reuber et al, 2001) and 0.8-2.55 mm (Lalas et al, 2012). Tansi et al (2017) reported seed length of 1.26-2.21 mm and seed width of 1.18-2.00 mm in Crambe orientalis, and seed length of 2.02-2.88 mm and seed width of 1.86-2.83 mm in Crambe tataria. These values are similar to those obtained in own studies.…”
Section: Geometric Properties Of Crambe Seedsmentioning
confidence: 84%
See 1 more Smart Citation
“…In other studies, the diameter of crambe (Crambe abyssinica) seeds was 2.7 mm (Reuber et al, 2001) and 0.8-2.55 mm (Lalas et al, 2012). Tansi et al (2017) reported seed length of 1.26-2.21 mm and seed width of 1.18-2.00 mm in Crambe orientalis, and seed length of 2.02-2.88 mm and seed width of 1.86-2.83 mm in Crambe tataria. These values are similar to those obtained in own studies.…”
Section: Geometric Properties Of Crambe Seedsmentioning
confidence: 84%
“…The values of 1000 seed weight of crambe, determined in this study, are similar to those found in the available literature. Reuber et al (2001) reported a value of 6.2 g. In a study by Zanetti et al (2013), the 1000 seed weight of crambe (Crambe abyssinica) reached 6.00-7.50 g, whereas Tansi et al (2017) reported that the 1000 seed weight of crambe ranged from 6.00 to 9.98 g in Crambe orientalis up to 17.80 g in Crambe tataria. Comparing with the available literature data, the densities of crambe seeds determined in own studies are lower than the values obtained for other oilseed species, e.g.…”
Section: Physical Properties Of Crambe Seedsmentioning
confidence: 98%
“…Similar to the results of our study, the main compounds in C. orientalis oil were found as erucic acid (30.33 %), oleic acid (10.83 %), linoleic acid (10.68 %), and cis-11 eicosenoic acid (8.71 %). [16] The Enzyme Inhibition Results of Crambe orientalis Plant Enzyme Inhibition (IC 50 Values) Against Collagenase, a-Glycosidase, Tyrosinase, and Urease…”
Section: Total Phenolic Content (Tpc) and Total Flavonoid Content (Tf...mentioning
confidence: 99%
“…In addition, Crambe oil is used in the steel industry for making steel plate, in the textile, perfume, detergent, pesticide industries, and the production of printer ink. In addition, it has been reported that this plant is an intermediate host to many insect species [4] . Crambe oil can then be converted into several industrial and energy uses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation